Optimizing Workforce Productivity Through Human Resource Development: Insights from PT Telkom Indonesia Tbk - Burhanuddin, Burhanuddin (Abadi Institute, 2024)
The main objective of this research is to analyze the human resource empowerment strategies used by PT Telkom Indonesia Tbk and their impact on work productivity. Data was collected through interviews with company management, employees, and industry experts competent in this field. This research employs a qualitative approach and utilizes data collection techniques such as observation and literature study. The results of the study indicate that PT Telkom Indonesia Tbk has implemented various effective human resource empowerment strategies. Telkom has implemented several programs aimed at improving work productivity. These include providing career development opportunities, employee training and development, rewards and incentives for employees, as well as conducting performance appraisals. The implementation of these human resource empowerment strategies has had a positive impact on work productivity at PT Telkom Indonesia Tbk. The research concludes that effective human resource empowerment strategies can help improve company work productivity. The findings of this study can provide insights and recommendations for other companies seeking to enhance work productivity through human resource empowerment.